ORAL IRON-HYDROXIDE POLYMALTOSE COMPLEX VERSUS SUCROSOMIAL IRON FOR CHILDREN WITH IRON DEFICIENCY WITH OR WITHOUT ANEMIA: A CLINICAL TRIAL WITH EMPHASIS ON INTESTINAL INFLAMMATION - Sonia Alexiadou; Christina Tsigalou; Eleni Kourkouni; Aggelos Tsalkidis; Elpis Mantadakis (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Iron deficiency anemia (IDA) is a major public health problem among children worldwide. Iron deficiency without anemia (IDWA) is at least twice as common as IDA. Some studies propose that oral iron fortification can modify the infant’s gut microbiome leading to intestinal inflammation.